Reflective journal writing and interpreting anxiety: insights from a longitudinal study - Wang, Zhenzhen (Frontiers in Psychology, 2025)
This mixed study explores the impact from reflective journal writing upon students' interpreting anxiety. It draws on data sources from students' reflective journals written during the semester as well as two questionnaires of Anxiety Scale for Chinese Interpreting Learners. The study focuses on three dimensions of interpreting anxiety, namely task anxiety, error anxiety and confidence anxiety. Task anxiety has been significantly alleviated over the course, while the other two have not. The cognitive–affective–behavioral intervention mechanism identified in students' reflective journals, functions effectively in mitigating interpreting anxiety. The study also reveals how instructed reflective journals enable students to perceive themselves as self-motivated and sustainable learners. This study holds important pedagogical implications for educators in language teaching and other educational context.